Audit expectation gap in relation to fraud prevention and detection in Nigeria - Sule, Safiyanu (2020)
Audit expectation gap (AEG) refers to the difference between what the users of financial statements perceive as auditors‟ responsibilities and what auditors believe their responsibilities are. This study investigates, firstly, perceptions on the existence, causes and possible solutions of AEG in relation to fraud prevention and detection in Nigeria, secondly, perceptions on whether AEG is caused by a knowledge gap or performance gap. This study employs a qualitative research method; where data were collected through interviews and documents (including website). The interviews were conducted with 3 regulators, 4 professional accounting bodies, 7 practicing auditors, 8 investors, and 3 corporate directors. Utilizing role theory and stakeholder theory, the findings reveal that AEG in relation to fraud prevention and detection still exists in Nigeria. The findings indicate that the causes of the gaps are linked to the role conflicts in three areas; inter-role conflict by users‟ conflicting expectations on the roles of auditors; intra-role conflict by users‟ incompatible expectations on the nature of auditors‟ report, and subjective-role conflict by the deficient performance of auditors. The analysis also identified possible solutions for reducing the existence of AEG through educating users about the roles and responsibilities of auditors and possible adoption of ISA 700 into financial reporting practice. This study contributes to AEG literature by providing new insights into the impact of ISA 700 on reducing the AEG in a developing country. The findings provide evidence of AEG existence and enable regulators to provide appropriate measures to reduce such gaps. The study recommends policymakers to educate the general public about the functions of an audit and the work of auditors. The monitoring of auditors‟ performance should also be strengthened to narrow the deficient performance gap. The adoption of ISA 700 also could improve public‟s understanding of the responsibilities of auditors and management.